A simulation approach to validating optimized kitchen layouts: Reassessing the work triangle through real apartment floor plan analysis. - Lee, Jane; Ryu, Eunseo; Kim, Jun Young; Lee, Joong Hee; Yun, Myung Hwan (Work, 2025)
Background: The conventional Work Triangle principle has long been a guiding concept in kitchen design, aiming to optimize workflow and minimize workload. However, with the advent of modern appliances and evolving lifestyles, the effectiveness of the Work Triangle in addressing the diverse activities and needs of contemporary kitchens is increasingly limited. Objective: This study aims to verify the validity of the Work Triangle in modern kitchen design and propose a kitchen modeling algorithm that facilitates customization based on layout and the area size from a user-centered perspective. Methods: The research was conducted in two parts. In the first part, the validity of the Work Triangle was verified through the analysis of 38 actual apartment kitchen floor plans in Korea. Then the second part, a kitchen layout optimization model was developed using 0–1 integer programming to minimize the distance between kitchen appliances, incorporating the placement of modern appliances not included in the traditional Work Triangle. Results: The statistical analysis of kitchen floor plans data showed that the impact of Work Triangle compliance on movement efficiency was limited, suggesting the need for customized kitchen design that reflects user behavior patterns and the placement of modern appliances and storage spaces. The model was evaluated through simulation, demonstrating its effectiveness in optimizing kitchen appliances layout. Conclusions: The study emphasizes the need to consider actual usage patterns and the limitations of the Work Triangle in modern kitchen design, proposing a user-centered optimization model that enables customization based on individual cooking scenarios and lifestyles.